Jurisprudential analysis of reiterated child sexual abuse: continued crime vs. real competition (Papeles, 2025)
This work analyzes the jurisprudence of the Superior Court of Justice of the province of Córdoba regarding the crime of sexual abuse repeated over time when the victim is a child or adolescent. It is discussed whether these acts should be classified as a continuing crime or whether the rules of the real competition apply. On many occasions, the courts apply the figure of a continuing crime whose criminal scale is lower than that of material competition, without considering the special vulnerability of the minor victims who suffer abuse, who suffer it - most of the time - without the presence of witnesses, with the aggressor being able to reiterate it as many times as possible. The hypothesis that is deduced is that, when there is a plurality of similar harmful acts, carried out against the sexual integrity of the same minor and perpetrated by the same aggressor, the scale corresponding to the actual contest must be applied. To this end, doctrine and jurisprudence of the Superior Court of Justice of the province of Córdoba on the combination of crimes and continued crime and the legal right protected in sexual abuse will be examined.
Keywords: Sexual abuse; continued crime; concurrent crimes; proportionality of the sentence; sexual integrity